Droplet Impact Behaviour of Modified Geopolymer Solution on Urea Surface - A. Majid, Maizan Amani (IRC, 2016)
Geopolymer is a compound formed by the alkali silicate activation of aluminosilicate materials. In this research project, geopolymer is proposed as the new controlled release fertilizer (CRF) coating material as it exhibits specific properties to improve CRF coating, eco-friendly and manufactured through sustainable production process. Thus, the droplet impact behaviour of geopolymer is studied in this research project to determine the wettability of the geopolymer solution on the urea surface by identifying the contact angle, surface tension and maximum spreading factor of the geopolymer droplet. Besides that, small amount of nanoclay is added as filler into the geopolymer solution and the effect of adding nanoclay towards the geopolymer wettability is also being studied.